2014
DOI: 10.5152/eurjrheumatol.2014.036
|View full text |Cite
|
Sign up to set email alerts
|

Skin imaging in systemic sclerosis

Abstract: Fibrotic involvement of the skin is a cardinal feature of systemic sclerosis (SSc). The extent of skin involvement is associated with internal organ involvement, coinciding with more severe disease course and poor prognosis. A palpation-based semi-quantitative score, the modified Rodnan skin score, is widely used for the assessment of skin involvement, but it is entailed by significant limitations. More objective approaches to measure skin involvement employing imaging have been explored continuously in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…With a progress in diagnostic imaging, researchers focused their interest on the applicability of ultrasonography for the evaluation of the severity and extent of skin fibrosis in SSc [13,14]. The ultrasound elastography is an ultrasonographic technique suitable for the quantification of skin fibrosis, indicating not the thickening of the skin, but its strain-a parameter, which can be considered as a more detailed marker of a change of the skin structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…With a progress in diagnostic imaging, researchers focused their interest on the applicability of ultrasonography for the evaluation of the severity and extent of skin fibrosis in SSc [13,14]. The ultrasound elastography is an ultrasonographic technique suitable for the quantification of skin fibrosis, indicating not the thickening of the skin, but its strain-a parameter, which can be considered as a more detailed marker of a change of the skin structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…Suliman et al (2018) recently characterized skin ulcers by means of the ultrasound technique (grayscale and Doppler study) [21]. Studies have shown reliable results with good inter-/intra-observer variability of this imaging method [22]. While the current study investigated a number of biomechanical indices in patients with scleroderma and made comparisons with age-and BMI-matched healthy subjects, it has some limitations.…”
Section: Discussionmentioning
confidence: 97%
“…Ultrasound imaging (UI) has been used to assess the dermal thickness (DT) and echogenicity in SSc patients, which has been validated with the site‐specific mRSS (SMRSS) performed by an experienced dermatologist . Hesselstrand et al reported moderate correlations of UI‐assessed skin thickness and an SMRSS of 0.37, 0.72 and 0.65 for the finger, hand and forearm, respectively.…”
Section: Introductionmentioning
confidence: 99%